HUBUNGAN FAKTOR STRESS, KETERATURAN MAKAN DAN KONSUMSI MAKANAN ATAU MINUMAN IRRITATIF TERHADAP KEJADIAN SINDROM DISPEPSIA - Adriyani Adam; Mustamin Mustamin; zakaria zakaria; Hikmawati Mas'ud; Nurkhairunnisa Nurkhairunnisa (Media Gizi Pangan, 2023)
Dyspepsia syndrome is one of the many digestive tract disorders which is often a complaint and is a public health problem. The incidence of dyspepsia in 2021 is expected to increase from 10 million to 28 million people, accounting for 11.3% of the total population in Indonesia. The purpose of this study was to determine the relationship between stress factors, eating regularity, and consumption of irritative food or drinks on the incidence of dyspepsia syndrome in final year students of D.IV Study Program, Poltekkes Kemenkes Makassar.This research is an analytical research with a cross sectional approach. The research was conducted online at the Department of Physiotherapy, Dental Nursing, partly for the Department of Environmental Health, Medical Laboratory Technology, Pharmacy and Nutrition and offline partly for the Department of Environmental Health, Nutrition, Pharmacy and Medical Laboratory Technology. The research was conducted in November 2022 - February 2023. The research sample was final year students of the Makassar Ministry of Health Poltekkes with a total of 198 people using a random sampling system. Data on stress factors, eating regularity, consumption of irritative food or drinks and dyspepsia syndrome were obtained using a questionnaire. Data from the results of this study were processed by statistical tests using the chi-square test.The results showed that there was a relationship between stress level and the incidence of dyspepsia syndrome (P = 0.00), there was no relationship between eating regularity and the incidence of dyspepsia syndrome (P = 0.257), there was no relationship between consumption of irritative food or drink with the incidence of dyspepsia syndrome (P = 0.440).Suggestions for students to motivate themselves to consume food regularly, reduce consumption of irritating foods or drinks, and habits that can cause stress in order to avoid dyspepsia syndrome.Keywords        : irritative , stress, dyspepsia syndrome.